2021
DOI: 10.5500/wjt.v11.i6.203
|View full text |Cite
|
Sign up to set email alerts
|

Hyperkalemia: Major but still understudied complication among heart transplant recipients

Abstract: Hyperkalemia is a recognized and potentially life-threatening complication of heart transplantation. In the complex biosystem created by transplantation, recipients are susceptible to multiple mechanisms for hyperkalemia which are discussed in detail in this manuscript. Hyperkalemia in heart transplantation could occur pre-transplant, during the transplant period, or post-transplant. Pre-transplant causes of hyperkalemia include hypothermia, donor heart preservation solutions, conventional cardioplegia, normok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Although recognized as a life-threatening complication, the literature supporting the link between tacrolimus and hyperkalemia is limited to mechanistic reviews and case reports in cardiothoracic transplantation [ 11 , 14 ]. A retrospective study in kidney transplant patients found increased hyperkalemia in patients taking tacrolimus vs cyclosporine [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although recognized as a life-threatening complication, the literature supporting the link between tacrolimus and hyperkalemia is limited to mechanistic reviews and case reports in cardiothoracic transplantation [ 11 , 14 ]. A retrospective study in kidney transplant patients found increased hyperkalemia in patients taking tacrolimus vs cyclosporine [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical intervention for hyperkalemia typically occurs before potassium levels reach 5.5 mmol/L in heart and lung transplantation due to risk of life-threatening arrhythmias. After cardiac surgery, the optimum range is often defined as 3.8–4.3 mmol/L [ 11 ]. Therefore, we chose 5.0 mmol/L as our defined breakpoint for hyperkalemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation